Endovascular repair of innominate artery true aneurysm with extra-anatomic revascularization of right carotid and vertebral arteries — A case report - Chang, John B.; Stein, Theodore; Siegel, David; Rosca, Mihai (International Journal of Angiology, 2005)
The purpose of this article is to describe the endovascular repair of a large aneurysm of the innominate artery in a patient with a history of chronic renal failure and coronary artery bypass. A 4.5 × 4.8-cm innominate artery aneurysm that extended to the proximal subclavian artery was diagnosed by chest X-ray, computed tomography, computed tomography angiography, and aortic arch angiogram in an 80-year-old man who had problems with his angio access for renal dialysis. Since these aneurysms are potential sources of emboli to the brain, extra-anatomic diversion and revascularization of the right carotid and vertebral arteries were done before endovascular manipulation of the innominate artery. Before discharge, a computed tomography scan showed no evidence of a Type I or major Type II leak. The patient has been doing well as an outpatient. Large innominate artery aneurysms in high-risk patients can be treated successfully by using a combined approach of extra-anatomic revascularization of the right carotid and vertebral artery system, and endovascular repair of the aneurysm.